1974
DOI: 10.1093/jaoac/57.3.513
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Study of the Rat Hemoglobin Repletion Test for Bioavailability of Iron

Abstract: A collaborative study of the hemoglobin repletion test was conducted with male weanling rats. The rats were depleted for 4 weeks on a low-iron casein based diet. They were then divided into 13 comparable groups of at least 8 animals each. One group continued on the basal diet. Three groups were given different levels of each of 4 samples. Sample 1 was FeS04.7H20, used as the reference standard. Samples 2 and 3 were from the same lot of electrolytically reduced iron separated into fractions of different particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The encapsulation processes and materials used in the study had little effect on iron bioavailability in vitro as well as in vivo [26,27]. The hemoglobin repletion assay in rats confirmed that microencapsulated ferrous fumarate made by fluidized-bed agglomeration and lipid coatings had a bioavailability of 95% [17].…”
Section: Discussionmentioning
confidence: 97%
“…The encapsulation processes and materials used in the study had little effect on iron bioavailability in vitro as well as in vivo [26,27]. The hemoglobin repletion assay in rats confirmed that microencapsulated ferrous fumarate made by fluidized-bed agglomeration and lipid coatings had a bioavailability of 95% [17].…”
Section: Discussionmentioning
confidence: 97%
“…This standard method is the recommended in vivo method for accurately predicting human bioavailability of iron compounds. 27,50,51 The toxicity results of our feeding studies with these compounds are reassuring, but only low doses of iron were given for a short period. Certainly, more systematic research on the safety of these and other nanostructured compounds is required.…”
Section: Conclusion and Recommendations For Future Researchmentioning
confidence: 95%
“…In this method, weanling rats are made anemic by feeding low Fe diets, and then are fed graded doses of the different Fe compounds or FeSO 4 , the Hb repletion rates are compared, and the relative bioavailability (RBV) of an Fe compound is expressed as the rate of Hb repletion relative to the repletion rate from FeSO 4 . 27,50,51 For the in vivo tests, we chose five of the Fe and Fe/Zn compounds that were both highly soluble in dilute acid and had good sensory qualities in foods (Table 1). A Fe/Zn phosphate (FePO 4 /Zn 3 (PO 4 ) 2 ) and a Fe/Zn oxide (Fe 2 O 3 /ZnO) were compared to investigate the influence of phosphate on iron bioavailability.…”
Section: In Vivo Bioavailability Studiesmentioning
confidence: 99%
“…More limited definitions are used also (Van Dokkum, 1992). Fe bioavailability may be assessed using the so-called rat haemoglobin(Hb)-repletion bioassay, which is the official method of the Association of Official Analytical Chemists (Fritz et al 1974;Association of Official Analytical Chemists, 1990). This assay involves the determination of the increase in blood Hb concentrations in rats with Fe-deficiency-induced anaemia after the administration of a diet containing the Fe compound under study relative to the reference source of Fe, i.e.…”
mentioning
confidence: 99%